উদ্ধৃতি-অভিধান - মিত্র, দীলিপ কুমার (কলকাতা : পারুল প্রকাশনী, 2012)
Collection of quotations from the works of various 19th and 20th century Bengali authors, arranged under topics.
নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
Keywords: Quotations, Bengali; Bengali literature; Citations bengali